Mitochondrial DNA Copy Number Raises the Potential of Left Frontopolar Hemodynamic Response as a Diagnostic Marker for Distinguishing Bipolar Disorder From Major Depressive Disorder - Tsujii, Noa; Otsuka, Ikuo; Okazaki, Satoshi; Yanagi, Masaya; Numata, Shusuke; Yamaki, Naruhisa; Kawakubo, Yoshihiro; Shirakawa, Osamu; Hishimoto, Akitoyo (Frontiers in Psychiatry, 2019)
Background: Given a lack of markers, diagnoses of bipolar disorder (BD) and major depressive disorder (MDD) rely on clinical assessment of symptoms. However, the depressive mood states of BD and depressive symptoms of MDD are often difficult to distinguish, which leads to misdiagnoses, which in turn lead to inadequate treatment. Previous studies have shown that the hemodynamic responses of the left frontopolar cortex measured by near-infrared spectroscopy (NIRS) differ between BD and MDD; these hemodynamic responses are associated with altered mitochondrial metabolism; and mitochondrial DNA copy number (mtDNAcn), an index of mitochondrial dysfunction, tends to decrease in BD and increase in MDD patients. In this study, we confirmed that mtDNAcn trends in opposite directions in BD and MDD. We then determined whether mtDNAcn could enhance the utility of NIRS as a diagnostic marker to distinguish between BD and MDD. Methods: We determined mtDNAcn in peripheral blood samples from 58 healthy controls, 79 patients with BD, and 44 patients with MDD. Regional hemodynamic responses during a verbal fluency task (VFT) in 24 BD patients and 44 MDD patients, matched by age and depression severity, were monitored using NIRS. Results: Measurements of mtDNAcn were lower in BD patients and higher in MDD patients than in controls. The left frontopolar region exhibited the most significant differences in mean VFT-related oxy-Hb changes between the BD and MDD groups. Multivariate logistic regression analysis with variables including age, sex, hemodynamic response of the left frontopolar region and mtDNAcn showed high accuracy for distinguishing BD from MDD (area under the curve = 0.917; 95% confidence interval = 0.849–0.985). For the BD group, we observed a positive correlation between hemodynamic responses in the left frontopolar region and mtDNAcn, while for the MDD group, we observed a negative correlation. Conclusions: Our findings suggest that the association between hemodynamic response and mitochondrial dysfunction in BD or MDD plays an important role in differentiating the pathophysiological mechanisms of BD from those of MDD.